Gender Paradox in Psychological Dating Violence in Indonesian Urban Adolescents: A Differential Item Functioning Analysis - Suci Musvita Ayu; Erni Gustina; Teti Lisdiyanti; Ardyawati Wira Oktaviana; Zulva Ferdiana Kulsum; Moh. Irma Sukarelawan; Liena Sofiana (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The gender paradox can be described as when violence against boys is considered minor, while violence against girls is considered oppression. What are the experiences of psychological dating violence among urban adolescents in Indonesia, and how can these be evaluated using Rasch modelling? Methods: This study used a cross-sectional survey approach with 114 junior high school students in private schools in Yogyakarta. The instrument used was the 10-PDV. The psychological violence paradox in adolescent dating was analyzed using the Mann-Whitney U test and Differential Item Functioning (DIF). Gender paradoxes were assessed based on p-value, DIF contrast, Rasch-Welch t, and Mantel-Haenszel Prob. Results: The results of the study indicate the normalization of unhealthy behavior among urban adolescents in dating relationships, with a prevalence of psychological violence exceeding 50%. On the one hand, the percentage of female adolescents reporting psychological violence was higher than that of male adolescents. On the other hand, adolescent boys reported experiencing psychological violence with a higher severity level compared to adolescent girls. Conclusion: These findings indicate a gender paradox in urban adolescent psychological dating violence.